2015
DOI: 10.1158/1078-0432.ccr-14-3323
|View full text |Cite
|
Sign up to set email alerts
|

HPV Serum Antibodies as Predictors of Survival and Disease Progression in Patients with HPV-Positive Squamous Cell Carcinoma of the Oropharynx

Abstract: Purpose Oropharyngeal carcinoma (OPC) positive for human papillomavirus type 16 (HPV16) has a significantly better prognosis than OPC unrelated to HPV. Within HPV16-positive OPC, biomarkers of prognosis are urgently needed to individualize care. We hypothesized that serum antibodies specific to HPV16, the major HPV type causing OPC, have biological relevance and are potential biomarkers for improved prognosis among patients with HPV16-positive OPC. Methods IgG antibodies to the HPV16 antigens E1, E4-E7, L1, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 25 publications
7
60
1
2
Order By: Relevance
“…1; Table 3), although not statistically significant. These findings are in contrast with a recent report from MD Anderson which noted lower median antibody levels among 8 patients with recurrence than 23 patients without recurrence [20]; (Supplemental Table 4). …”
Section: Discussioncontrasting
confidence: 99%
“…1; Table 3), although not statistically significant. These findings are in contrast with a recent report from MD Anderson which noted lower median antibody levels among 8 patients with recurrence than 23 patients without recurrence [20]; (Supplemental Table 4). …”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the findings of the current study, the median antibody levels of individuals who recurred or did not recur were statistically similar and appeared to be (non-significantly) lower for patients who recurred. Of note, consistent with our findings, a decline in median antibody levels is apparent graphically when comparing pre-treatment and post-treatment levels (25). …”
Section: Discussionsupporting
confidence: 90%
“…Indeed other head and neck cancers which are not HPV-related are not expected to be HPV seropositive (24), and therefore any associations observed may be driven by the majority seronegative and low levels of antibodies. A similar approach of restricting to HPV-positive OPCs (determined by PCR) was recently used to demonstrate that the presence of HPV E6 serum antibodies at diagnosis was significantly associated with improved overall and progression-free survival (25). In contrast to the findings of the current study, the median antibody levels of individuals who recurred or did not recur were statistically similar and appeared to be (non-significantly) lower for patients who recurred.…”
Section: Discussionmentioning
confidence: 99%
“…[22] The examination of post-treatment oral rinses by Rettig et al [23] has specific merit, as this study showed the ability to detect HPV16 DNA in the oral rinses of 5 patients who developed recurrence of their cancer. They showed high specificity for local disease recurrence (median time from earliest post-treatment detection to recurrence: 7 months), suggesting that this biomarker be used in subsequent surveillance protocols.…”
Section: Discussionmentioning
confidence: 99%